John Adolphus Bernard Dahlgren papers - Dahlgren, John Adolphus Bernard, 1809-1870.
Family correspondence, consisting primarily of letters from Dahlgren on board the U.S.F. Cumberland in the Mediterranean (1843-1845) to his wife, Mary Bunker Dahlgren, describing places, persons, and social events. Includes letters of his daughter Eva Dahlgren, and of his second wife, Sarah Madeleine Vinton Dahlgren.
Naval officer.
Forms part of: Naval Historical Foundation collection.
Keywords: Dahlgren, Eva -- Correspondence; Dahlgren, Mary Bunker -- Correspondence; Dahlgren, Sarah Madeleine Vinton, -- 1825-1898 -- Correspondence; United States. -- Navy -- Foreign service -- Mediterranean Region; Cumberland (Frigate); Mediterranean Region -- Description and travel; Naval officers